Monographs in Oral Science 2000
DOI: 10.1159/000061643
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Oral Cavity Using Optical Coherence Tomography

Abstract: Optical coherence tomography is a new method for noninvasively imaging internal tooth and soft tissue microstructure. The intensity of backscattered light is measured as a function of depth in the tissue. Low coherence interferometry is used to selectively remove the component of backscattered signal that has undergone multiple scattering events, resulting in very high resolution images (< 15 microns). Lateral scanning of the probe beam across the biological tissue is then used to generate a 2-D intensity plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…8(c) and 8(d). The depth profiles show a clear demarcation of two layers with distinctly different attenuation slopes within the enamel, indicating pre and post-natal enamel formation [27]. The scattering coefficients calculated from the depth profiles are 0.8 mm −1 and 0.3 mm −1 in the pre-natal enamel layer and 0.7 mm −1 and 0.8 mm −1 in the post-natal enamel layer, at λ = 1.3 µm and 1.7 µm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…8(c) and 8(d). The depth profiles show a clear demarcation of two layers with distinctly different attenuation slopes within the enamel, indicating pre and post-natal enamel formation [27]. The scattering coefficients calculated from the depth profiles are 0.8 mm −1 and 0.3 mm −1 in the pre-natal enamel layer and 0.7 mm −1 and 0.8 mm −1 in the post-natal enamel layer, at λ = 1.3 µm and 1.7 µm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While some research has been reported in ophthalmologic, dermatologic, GI, gynecological, cardiac, and other OCT applications [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], there is limited information on intra-oral OCT, mainly on the topics of periodontal disease and hard tissue pathology, up to this time [30][31][32][33].…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…OCT is being evaluated for use in imaging oral tissue [52,53]. Using a hamster cheek-pouch mode of oral carcinogenesis, Wilder-Smith et al [53] demonstrated differences between normal and dysplastic epithelium using OCT.…”
Section: Diagnostic Aidsmentioning
confidence: 99%